Referee`s bias explain red color advantage in taekwondo - Carazo-Vargas, P.; Moncada-Jimenez, J. (Journal of Physical Education and Sport, 2014)
Previous research supports the notion that wearing red color uniforms enhances human performance in sports competitions; however, such results might have been contaminated by referees` bias. The purpose of this study was to evaluate the influence red color in taekwondo fights when athletes wore a vest linked to an automatic scoring system. We evaluated 718 fights from the World Taekwondo Championships 2013. Potential moderator variables gender, weight category, competition round, victory method, and performance asymmetry were evaluated. A one sample binomial test revealed that the proportion of winning a combat was similar when wearing red or blue uniforms (p = 0.478). A multiple logistic regression analysis failed to explain the influence of moderator variables in winning a combat (R2 = 0.04). In conclusion, red color does not enhance human performance in Taekwondo. Previous research showing otherwise might have been biased by human error in refereeing.